(untitled) (Jurnal Ipteks Terapan, 2024)
The development of technology and information provides changes and convenience in human life. Technology that we often use in our daily lives such as television, mobile phones, DVDs and other forms of screen media. Nowadays, it is easier for children to access digital media or screen time to play games, read books and watch TV. This systematic review aims to assess, identify and describe studies that focus on the impact of screen time exposure on sleep patterns in toddlers. The method of searching research articles through the electronic databases Pro quest, Spinger Link, SAGE journals, Scopus, Science Direct and PubMed which were published in 2018 - 2023 found 10 articles that were included in the analysis list. The article has gone through a study selection process using PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). PICO/PEO in this systematic review is whether the impact of screen time exposure on sleep patterns of toddlers. The results of the study indicate that excessive use of screen time causes poor sleep quality in children. The most important criteria for children’s sleep quality are the number of awakenings at night, difficulty sleeping at night and total sleep time of at least 9 hours. Conclusion: screen time exposure and sleep habits have an effect on children’s sleep quality. Implications: need for efforts to provide education to the public to limit the use of digital media in toddlers